Cell death regulation but not abscisic acid signaling is required for enhanced immunity to Botrytis in Arabidopsis cuticle-permeable mutants. (22nd July 2019) - Cui, Fuqiang; Wu, Wenwu; Wang, Kai; Zhang, Yuan; Hu, Zhubing; Brosché, Mikael; Liu, Shenkui; Overmyer, Kirk
Abstract : An Arabidopsis farnesyl transferase loss-of-function mutant exhibited a permeable cuticle and enhanced immunity to Botrytis . This immunity was fully suppressed by loss of function of the cell death regulator BOTRYTIS SENSITIVE1. Abstract: Prevailing evidence indicates that abscisic acid (ABA) negatively influences immunity to the fungal pathogen Botrytis cinerea in most but not all cases. ABA is required for cuticle biosynthesis, and cuticle permeability enhances immunity to Botrytis via unknown mechanisms. This complex web of responses obscures the role of ABA in Botrytis immunity. Here, we addressed the relationships between ABA sensitivity, cuticle permeability, and Botrytis immunity in the Arabidopsis thaliana ABA-hypersensitive mutants protein phosphatase2c quadruple mutant ( pp2c-q ) and enhanced response to aba1 ( era1-2 ). Neither pp2c-q nor era1-2 exhibited phenotypes predicted by the known roles of ABA; conversely, era1-2 had a permeable cuticle and was Botrytis resistant. We employed RNA-seq analysis in cuticle-permeable mutants of differing ABA sensitivities and identified a core set of constitutively activated genes involved in Botrytis immunity and susceptibility to biotrophs, independent of ABA signaling. Furthermore, botrytis susceptible1 ( bos1 ), a mutant with deregulated cell death and enhanced ABA sensitivity, suppressed the Botrytis immunity of cuticle permeable mutants, and this effect was linearly correlated with the extent of spread of wound-induced cell death in bos1 . Overall, our data demonstrate that Botrytis immunity conferred by cuticle permeability can be genetically uncoupled from PP2C-regulated ABA sensitivity, but requires negative regulation of a parallel ABA-dependent cell-death pathway.